Rutin: A Flavonoid as an Effective Sensitizer for Anticancer Therapy; Insights into Multifaceted Mechanisms and Applicability for Combination Therapy. (23rd August 2021) - Satari, Atefeh; Ghasemi, Sorayya; Habtemariam, Solomon; Asgharian, Shirin; Lorigooini, Zahra
Abstract : Rutin is a unique antioxidant flavonoid that is mainly found in fruit, vegetables, cereals, and many other plant-based human diets. This review aims to highlight the in vitro anticancer properties of rutin including combination therapeutic strategies. Literature resources were gathered through PubMed, Scopus, Web of Science, and Google Scholar databases that cover the period of 1995–2021. Rutin is demonstrated to inhibit the proliferation of breast, colon, lung, and prostate cancers and other tumors. Furthermore, rutin alone or in combination with other therapeutic agents has been shown to regulate several signalling pathways involving the Ras/Raf and PI3K/Akt, MAPK, and TGF- β 2/Smad2/3Akt/PTEN, etc., which are related to the processes of carcinogenesis and induction of apoptosis. The combination of rutin with other chemotherapy drugs may benefit on prevention of tumor cells by decreasing drug resistance and chemotherapy side effects. Moreover, rutin induces apoptosis synergistically with the therapeutic agent. More in vivo and clinical data are however needed to evaluate the true potential of rutin as an anticancer agent as an adjuvant. The present review highlights the effects of rutin which can be a promising candidate in combination with other antitumor drugs or alone for cancer treatment in vitro . Also, rutin can lead to decrease in drug resistance and chemotherapeutic side effects.